Evaluation of the results of physical fitness tests and legal knowledge of basketball referees in Iraq in preparation for the basketball season 2019-2020 - Kareem, OdayAbdulhussein (International Journal of Psychosocial Rehabilitation, 2020)
Since the basketball game is one of the group games that need psychological, physical, technical and tactical aspects, so the search for ways to succeed in these important aspects was and is still ongoing. By conducting continuous tests for them to determine their levels from all sides, and here lies the importance of the research in reaching the level of the physical and cognitive abilities of basketball referees in Iraq. The Iraqi Basketball League between the governors of the province of Baghdad and the governors of the rest of the provinces, and here lies the research problem. Their own preparations for the 2019-2020 Premier League, as well as conducting a comparative study between the governors of Baghdad governorate and the central region on the one hand and the rulers of the southern and northern regions on the other hand in physical and cognitive abilities in preparation for the 2019-2020 Premier League. The conclusions of the research There was a discrepancy in the results of the physical and cognitive abilities tests for basketball referees, as well as a slight superiority in the results of the physical tests for the rulers of Baghdad and the central region.